Pentingnya Pendidikan Agama Kristen dalam Keluarga sebagai Sentral Belajar yang Bermisi - Ndruru, Sokhiziduhu (Sekolah Tinggi Teologi Hagiasmos Mission, 2019)
The family is the place of education first and foremost. It is in the family that children get the teachings of faith and moral values. In the old agreement, Christian Religious Education in families. This happened in the families of the ancestral fathers namely Abraham, Isaac, Jacob. They parents passed on faith to their descendants, even the entire nation of Israel. In the new covenant, the Lord Jesus as the Great Teacher who always teaches about faith to His listeners. The Christian family is a place to teach children faith. Some things that are done by Christian families to make their families as missions center is by making the family as the first place to spread the word of God, both through teaching and in the example of life. Abstrak Keluarga adalah tempat pendidikan yang utama dan terutama. Dalam keluargalah anak mendapatkan pengajaran iman dan nilai-nilai moral. Dalam perjanjian lama, Pendidikan Agama Kristen dalam keluarga-keluarga. Hal ini terjadi dalam keluarga-keluarga Bapa leluhur yaitu Abraham, Ishak, Yakub. Mereka orangtua mewariskan iman kepada keturunannya, bahkan seluruh bangsa Israel. Dalam perjanjian baru, Tuhan Yesus sebagai Guru Agung yang selalu mengajarkan tentang iman kepada para pendengar-Nya. Keluarga kristen adalah sebagai tempat untuk mengajarkan iman kepada anak-anak. Beberapa hal yang di lakukan oleh keluarga kristen untuk menjadikan keluarganya sebagai pusat bermisi adalah dengan cara menjadikan keluarga itu sebagai tempat pertama untuk menyebarkan firman Tuhan, baik itu melalui pengajaran maupun dalam teladan kehidupan.